Sepsis in obstetrics and gynecology (Perioperaciina Medicina, 2019)
Despite certain advances in modern medicine, the incidence of inflammatory diseases in women does not decrease, and infectious complications continue to occupy a leading place in the structure of obstetric and gynecological pathology. Moreover, the incidence of such dangerous complications as septic shock tends to increase. Over the past 25 years, the definition of sepsis and septic shock has changed three times; an international intensive care protocol is updated every four years with the participation of dozens of leading organizations and experts. Thus, the urgency of the problem is obvious and requires from doctors of all specialty’s modern knowledge on early detection and timely, early targeted therapy for sepsis and septic shock in obstetrics.
Keywords: sepsis; shock; infection; obstetrics; gynecology